A aprendizagem da docência nos cursos técnicos de ensino médio integrado - Baptaglin, Leila Adriana (2014)
The present thesis is part of the Training, Knowledge and Professional Development Research at the Program of Postgraduation in Education (PPGE) in the Federal University of Santa Maria (UFSM) which has its line and focuses on integrated learning of teaching technical courses in high school. It aims at understanding how is the learning of teaching by teachers who work with technical courses in high school is integrated. We seek thus to ascertain the formative processes of teachers working in the school culture and identify the implications on teacher s learning. This study uses qualitative methodology which will develop from the sociocultural narrative approach. The narratives of thirteen (13) teachers of integrated technical courses in high school (mechanical and electrical courses) from the Technical College investigated constitute the elements of analysis. Vygostki studies (1995 , 2003, 2007); Bakhtin (1986); Freitas (1994 , 1996, 1998); Bolzan (2002, 2006 , 2008, 2010 , 2011, 2013) and Connelly; Clandinin (1995) are the theoretical support underlying the investigative design of this research. The authors Isaia (2006 , 2007, 2009); Isaia; Bolzan (2008) ; Bolzan (2012 ); Maciel; Isaia; Bolzan (2012 ); Maciel (2009 ); Vygotsky (1993, 2005, 2007); Leontiev (1984); Davidov; Markova (1987) and Kosulin (2002) help us understand the fabric of the learning of teaching when discussing the teaching activity of study and training processes as stimuli for teacher learning. The discussion of school culture is outlined by authors such as Paro (2008 ); Nóvoa (2005); Minayo (2006); Bolzan (2002); Bolzan and Isaia (2007); Forquin (1993) and Vygotski (1995). The authors Frigotto, Ciavatta; Ramos (2005); Manfredi (2002); Regattieri; Castro (2009); Kunze (2009) and Kuenzer (1997) help us understand the professional and technological education and specific courses integrated to high school. In the analysis of the narratives teachers noted the existence of a large category: Learning of teaching, which consists of two dimensions, school culture and teaching culture . These dimensions are arranged from analysis axes/unfolding of dimensions which are structured by categorical elements. These elements are permeated by auxiliary stimuli arising from the research context and are mainstreamed by the teacher habitus. In this sense, it was evident throughout the study, collected through narratives, which in technical high school courses built this college belongs to a public IHE, the learning of teaching is much more the existence of a teacher habitus, which begins to reorganize school culture effectively than by the existence of a teaching activity study. Also evidenced, voltages that are essential for the learning of teaching, they are: individuality and colaboratividade; ownership of education and ownership of research and extension; general and specific training and teaching culture and school culture. We then, that in this process, measures are being taken, but there is still lack of articulation between school culture and teaching culture.